Apprenticeship of a mathematician - Weil Andre; Gage Jennifer (Basel Birkhauser Verlag, 1992)
This book includes very interesting recollections on the author's participation in the formation of the Bourbaki Group, tells of his meetings and conversations with leading mathematicians, reflects his views on mathematics. It describes an extraordinary
Translated from the French
Keywords: Andre Weil; Autobiographies; Biographies; France; Mathematicians